Wpływ agregacji danych na efektywność rynku giełdowego w Polsce - Jóźwicki, Rafał (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The goal of this paper is to examine the weak form efficiency of the Polish capital market represented by index WIG 20, using different periodicity (daily, weekly, and monthly). The author describes the Efficient Market Hypothesis: its weak, semistrong, strong forms and the methods of examination of the first of them. In order to verify the weak EMH, the author used simple trading rules based on the most popular technical analysis indicators: one moving average, two moving averages, MACD, RSI and stochastic oscillator. The researches were conducted on daily data from 2001 to 2006. The main conclusion says that changing periodicity in our investment strategy, we are not able to get better rate of return than by using passive strategy. This observation confirms the weak form efficiency of the Polish capital market in the period of time mentioned above. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 143-150